Long‐term sponge stranding along the shores of Sardinia Island (Western Mediterranean Sea). (30th October 2019) - Manconi, Renata; Padiglia, Andrea; Cubeddu, Tiziana; Pronzato, Roberto
Abstract: The taxonomic richness and geographic distribution of sponges stranded along Sardinian shores were investigated in the long term by means of a revisited ancient sampling method in order to support a comprehensive species inventory. Almost all stranded species were Keratosa ( n  = 20), plus 6 species of other Demospongiae taxa. Dictyoceratida were dominant, with 6 genera and 19 species of the families Irciniidae, Spongiidae and Thorectidae: 9 Mediterranean endemics, 7 Atlanto‐Mediterranean and 3 widespread species. Regarding Dendroceratida, only the genus Spongionella was found. Some species ( n  = 8) were recorded for the first time in circum‐Sardinian seas. A high percentage (54.3%; 19 out of the 35 species) of the total Mediterranean Dictyoceratida fauna was recorded, including the most endangered Mediterranean species, that is of the genera Spongia and Hippospongia . Hippospongia communis, Ircinia variabilis, Spongia zimocca and Spongia officinalis were the most common species. Morphotraits of rare and/or poorly known species were investigated by scanning electron microscopy (SEM). Comparison among Sardinian sectors, and between Sardinian and adjacent seas, revealed a high similarity of stranded Dictyoceratida, despite the fact that the data from Tyrrhenian and Balearic–Catalan seas were collected mainly from SCUBA records. The cost‐effective sampling method used in the present study seems appropriate to the gross qualitative monitoring of coastal areas (e.g. large unexplored Northern African coasts), in order to assess the conservation status of Mediterranean Keratosa species. The wide distribution of all Mediterranean bath sponge species indicates their good conservation status in circum‐Sardinian seas, a datum that could usefully support the future management of this bioresource, particularly in protected areas.